Counseling Needs of Secondary School Students and Their Learning Disorders - Alphonsa Diana Haokip; Tayum Saroh (Dera Natung Government College Research Journal)
The holistic development of a child is attainable in an environment conducive for teaching and learning and Barrell M.(2009) emphasized that the counselling needs of middle students can be addressed through counselling services and constructive learning strategies and methods. Thus, help and support can be availed to the students along their educational journey for their personal, emotional, and psychological growth. The educational setting inclusive of teachers, counsellors, and parents should ensure that holistic education is provided to the students as they undertake their academic endeavours. The learners of secondary schools consist of adolescents who are naive and vulnerable. They need backing to combat the complex challenges of modern life and cope with their pressing academic demands. Rathe (2014) opines that they are possessed by anxiety, mood swings, and intensity of feelings that adversely affect their learning. The present investigation focuses on the counselling needs of secondary students and their learning disorders that have adverse effects on their behaviour and academic performance (Mghweno,2015). This study highlights the need for considering the present educational scenario and the plight of traumatic experiences borne by the students. By exploring the current literature, it analyses studies conducted in India and abroad regarding the importance of establishing student counselling at secondary schools. The findings of the present study revealed how counselling can be instrumental to improve the learning styles of the students and the benefits they could reap from it. Further, the study unfolds the ways and means to tackle learning disorders of the students through counselling.